Enthalpy-Entropy Compensation in Polyester Degradation Reactions - Adam Al-Mulla (International Journal of Chemical Engineering)
In an earlier work the author had studied the degradation kinetics of polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT), and polybutylene terephthalate (PBT) under nonisothermal conditions in air and N2 at heating rates of 5, 10, 15, and 20°C/min. In this paper the kinetic degradation parameters of PET, PTT, and PBT were estimated using the Coats-Redfern method for two different weight loss regions ranging from 2–8% (Zone I) and 8–40% (Zone II). A comparative analysis of the enthalpy-entropy compensation effect for these polyesters in air and N2 is presented. A linear relationship was found to exist between entropy and enthalpy values. The following criteria were applied to establish an enthalpy-entropy compensation effect and to check the presence of an isokinetic temperature: (a) Exner’s plot of log k3T1 versus log k3T2, and (b) Krug et al. linear regression of ΔH versus ΔG. By the use of the latter two methods, varying isokinetic temperatures were obtained. These temperatures were not in the range of the experimental work conducted, indicating that these systems do not display compensation phenomena.